Comparison between video-lighted stylet (Intular Scope™) and direct laryngoscope for endotracheal intubation in patients with normal airway. Issue 11 (November 2020) - Lee, Ji Yeon; Hur, Ho Jin; Park, Hee Yeon; Jung, Wol Seon; Kim, Jiro; Kwak, Hyun Jeong
Objective: The Intular Scope™ (Medical Park, South Korea) (IS) is a video-lighted stylet that can be used for endotracheal intubation with excellent visualization by adding a camera to its end. We compared the efficacy of a direct laryngoscope (DL) with that of the IS based on hemodynamic changes, ease of intubation, and postoperative airway morbidities. Methods: Seventy patients with expected normal airways were randomized for intubation using an IS (n = 35) or DL (n = 35). The primary outcome was the mean arterial pressure during intubation. The secondary outcomes were the time to intubation (TTI), percentage of glottic opening (POGO) score, and number of intubation attempts. The incidence and severity of bleeding, hoarseness, and sore throat after intubation were also recorded. Results: Hemodynamic changes during intubation were not significantly different between the groups. The TTI was longer in the IS than DL group. The POGO score was higher in the IS than DL group. Hoarseness and sore throat were significantly less severe in the IS than DL group. Conclusions: Using the IS did not significantly improve hemodynamics and resulted in a longer TTI. However, the IS was associated with less severe postoperative airway morbidities compared with the DL.